IDENTIFIKASI BAKTERI PATOGEN PADA KUDA LAUT (Hippocampus kuda) DI BALAI BUDIDAYA LAUT, LAMPUNG - Yudha Trinoegraha Adiputra; Triyanto Triyanto; Namastra Probosunu (Jurnal Perikanan Universitas Gadjah Mada, 2005)
Sea horse (Hippocampus kuda) is one of the ornamental marine organisms and raw material of traditional medicine. Since 1993, Seafarming Development Centre, Lampung has pioneered a research and  culture  of sea horse in Indonesia. The serious problem in the culture of sea horse is pathogenic bacteria caused death of juveniles and broodstocks. The objective of this study was to identify pathogenic bacteria isolated from  sea horse in Seafarming Development Centre. Koch Postulate test was carried out, and then the pathogenic bacteria were identifed by morphological and biochemical tests. Results showed that from a total of 6 bacterial strains isolated from diseased sea horse, 3 strains were pathogenic bacteria to sea horse. These 3 pathogenic bacteria caused identical disease signs with the initial disease signs when the bacteria were isolated.  Morphological and biochemical tests suggested that  the pathogenic bacteria could be identified to be Vibrio fluvialis, V. alginolyticus and V. hollisae.